5-furan-2yl[1,3,4]oxadiazole-2-thiol, 5-furan-2yl-4H [1,2,4] triazole-3-thiol and their thiol-thione tautomerism - Koparir, M; Çetin, A; Cansiz, A (Molecular Diversity Preservation International, 2005)
5-Furan-2-yl[1,3,4]oxadiazole-2-thiol (Ia) and 5-furan-2-yl-4H-[1,2,4]triazole-3-thiol (Ib) were synthesized from furan-2-carboxylic acid hydrazide. Mannich bases and methyl derivatives were then prepared. The structures of the synthesized compounds were confirmed by elemental analyses, IR and H-1-NMR spectra. Their thiol-thione tautomeric equilibrium is described.
Keywords: 1,3,4-oxadiazoles; 1,2,4-triazoles; Mannich bases; thiol-thione tautomerism